Geomorphological Mapping of a Paraglacial Slope Instability at the Southeastern Tindfjallajökull Glacier, Iceland - Elías Arnar 1994- (2021)
This thesis is focused on a paraglacial slope instability by an outlet glacier at the southeastern part of Tindfjallajökull glacier, Iceland. A geomorphological mapping of the slope and the outlet glacier was conducted in order to determine the scale, possible causes and consequences of the deformation. A comprehensive literature review on paraglacial induced mass movement activity was conducted along with remote sensing methods for geomorphological analysis of the area throughout the 20th century. It was concluded that the process investigated resembles a paraglacial induced Deep Seated Gravitational Slope Deformation that has the potential to turn into a rapid slope failure. Further research is needed in order to confirm these findings and special emphasis should be put on field monitoring of the area while the process is still active. Results indicated that the retreat of the outlet glacier has an effect on the slope´s stability. The glacier is expected to continue its retreat at an exponential rate as global climatic warming is expected to continue. Climate change has and will most likely cause these processes to become more common in the future with a possible increase in paraglacial environments. In some cases, these processes are cause for concern as secondary effects such as Glacial Lake Outburst Floods (GLOFs) or tsunamis can pose severe natural hazards. Í þessari ritgerð verður rýnt í nærjökuls tengdan (e. paraglacial) óstöðugleika í norðurhlíð við jaðar skriðjökuls í suðaustur hluta Tindfjallajökuls. Kortlagning á landmótun hlíðarinnar ásamt skriðjöklinum fór fram með það að markmiði að skilgreina stærðargráðu, mögulega orsakavalda og afleiðingar þessa óstöðugleika. Gerð var yfirgripsmikil umfjöllun um stöðu þekkingar á nærjökuls tengdum hreyfingum í fjallshlíðum og breytilegri virkni þeirra. Fjarkönnunaraðferðum var síðar beitt við greiningu á landmótun- og breytingum á svæðinu á 20. öldinni. Niðurstöður sýndu að þeir ferlar sem eiga sér stað í hlíðinni sýna merki um DSGSD aflögun sem getur ...